2013
DOI: 10.1002/mren.201200075
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene/1‐Hexene Copolymerization with A Novel SiO2‐Supported Inorganic and Organic Hybrid Chromium‐based Catalyst

Abstract: In this work, ethylene/1‐hexene copolymerization with a novel SiO2‐supported inorganic and organic hybrid chromium‐based catalyst was investigated. This catalyst was prepared using the residual surface hydroxyl groups in Phillips catalyst to support bis(triphenylsilyl) chromate (BC) in order to get the merits from two important chromium‐based catalysts namely inorganic Phillips and organic S‐2 catalysts. The influences of addition amount of 1‐hexene and BC were systematically investigated. With increasing 1‐he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 46 publications
(56 reference statements)
2
18
0
Order By: Relevance
“…In order to further understand the effect of vanadium species on the modifi ed catalyst to the structure of polymer, the SCBD of the copolymers obtained from the original Mg/Ti catalyst and the V-modifi ed catalyst (MgV5:1/Ti catalyst) were compared by using the TREF+SSA method. [ 21,62 ] First, each copolymer was physically fractionated into several fractions based on crystallinity by TREF method according to the procedure described in the Experimental Section. Then the low (<40, 40-60, 60-70 °C) and the high (103-108, 108-115, 115-124 °C) temperature fractions were selected and characterized by HT-GPC as shown in Table 6 .…”
Section: The Comparison Of Scbd For Copolymers From Different Catalystsmentioning
confidence: 99%
“…In order to further understand the effect of vanadium species on the modifi ed catalyst to the structure of polymer, the SCBD of the copolymers obtained from the original Mg/Ti catalyst and the V-modifi ed catalyst (MgV5:1/Ti catalyst) were compared by using the TREF+SSA method. [ 21,62 ] First, each copolymer was physically fractionated into several fractions based on crystallinity by TREF method according to the procedure described in the Experimental Section. Then the low (<40, 40-60, 60-70 °C) and the high (103-108, 108-115, 115-124 °C) temperature fractions were selected and characterized by HT-GPC as shown in Table 6 .…”
Section: The Comparison Of Scbd For Copolymers From Different Catalystsmentioning
confidence: 99%
“…The ethylene/1‐hexene copolymers were fractionated by a self‐made TREF system . The equipment included an 850 mL column type fractionation bottle (height: 156 mm; diameter: 84 mm) filled with quartz sand, a silicone oil bath with thermostat (Huber, POLYTSTAT CC2‐225B ± 0.02 °C), a pump (KNF Lab, STEPDOS 08 S), a rotary evaporator (EYELA) and a nitrogen gas container.…”
Section: Methodsmentioning
confidence: 99%
“…This was similar to our previous report on the SiO 2 -supported inorganic and organic hybrid chromium-based catalyst. [23] It should be noted that a much sharper decrease in the kinetic profile associated to the fast formation and fast decay type. It was reported that the vanadium center in vanadium-based Ziegler-Natta polymerization system catalysts tended to rapidly deactivated due to overreduction to inactive lower oxidation states by Al-alkyl cocatalyst during the polymerization process.…”
Section: Ethylene Polymerization Behaviorsmentioning
confidence: 98%
“…The SCBD in the corresponding ethylene/1-hexene copolymer products was characterized by combination of temperature rising elution fractionation (TREF) with successive self-nucleation/annealing (SSA) as demonstrated in our previous reports. [23,35] 2. Experimental Section , and average pore size 24.5 nm) was donated by Qilu Branch Co., SINOPEC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation